Therapeutic Antibody-Induced Vascular Toxicity Due to Off-Target Activation of Nitric Oxide in Cynomolgus Monkeys. (25th February 2016) - Pai, Rama; Ma, Ning; Connor, Anu V.; Danilenko, Dimitry M.; Tarrant, Jacqueline M.; Salvail, Dany; Wong, Lisa; Hartley, Dylan P.; Misner, Dinah; Stefanich, Eric; Wu, Yan; Chen, Yongmei; et al.
Abstract: PRO304186, a humanized monoclonal antibody targeting soluble interleukin-17 A and F, was developed for autoimmune and inflammatory disease indications. When administered to cynomolgus monkeys PRO304186 induced unexpected adverse effects characterized by clinical signs of hematemesis, hematochezia, and moribundity. Pathology findings included hemorrhage throughout the gastrointestinal tract without any evidence of vascular wall damage or inflammatory cellular infiltration. Mechanistic investigation of these effects revealed mild elevations of serum MCP-1 and IL-12/23 but without a classical proinflammatory profile in PRO304186-treated animals. In vitro studies demonstrated off-target effects on vascular endothelial cells including activation of nitric oxide synthase leading to production of nitric oxide (NO) accompanied by increased mitochondrial membrane depolarization, glutathione depletion, and increased paracellular permeability. Additionally, endothelial cell-PRO304186-conditioned medium reduced myosin light chain phosphorylation in vascular smooth muscle cells. Furthermore, an ex vivo study utilizing segments from cynomolgus aorta and femoral artery confirmed PRO304186-induced endothelium-dependent smooth muscle relaxation and vasodilation mediated via NO. Finally, a single dose of PRO304186 in cynomolgus monkeys induced a rapid and pronounced increase in NO in the portal circulation that preceded a milder elevation of NO in the systemic circulation and corresponded temporally with systemic hypotension; findings consistent with NO-mediated vasodilation leading to hypotension. These changes were associated with non-inflammatory, localized hemorrhage in the gastrointestinal tract consistent with hemodynamic vascular injury associated with intense local vasodilation. Together, these data demonstrate that PRO304186-associated toxicity in monkeys was due to an off-target effect on endothelium that involved regional NO release resulting in severe systemic vasodilation, hypotension, and hemorrhage.